A dry udder in the milk season? Natural resource exploitation in Africa: realising the right to economic benefit to host communities - Van Reenen, Tobias P. (University of Pretoria, 2010)
Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of prof Tobias van Reeneen, Faculty of Law, University of Western Cape, South Africa.